Advantages and risks of using the google meet service for the conduct of online lessons - Kyselova, Olesia; Khmil, Nataliia; Chetaieva, Liudmyla (My University, 2022)
In the article, the authors highlight the relevance of the problem of using the Google Meet service for conducting online classes. Attention is drawn to the fact that, according to Google Trends, over the past three years, Google Meet has taken a leading position in Ukraine among the most popular video conferencing platforms. Emphasis is placed on the promising possibilities of this service in the educational process and its significant didactic potential. The active implementation of Google Meet in educational practice is due to its economic, technical, technological advantages, and didactic advantages. Important among them are the absence of fees for the use of the resource; intuitive interface; high level of security and quality of communication; the presence of a traffic and battery saving mode; ease of screen sharing to deliver documents, spreadsheets, or presentations, etc. Emphasis is placed on the advantages of organizing new forms of interaction between education seekers and teachers in the educational process: the possibility of chat is available; synchronization with contacts in the Google account; integration into various calendar planning systems; no time limit for video meetings; availability of Jambord virtual board; support for inclusive learning conditions and others. Considered additional benefits and advanced features of Google Meet available in Google Workspace for Education: scalability, availability of the «Video recording» function, organization of polling during the video meeting, breakout sessions, etc. At the same time, the authors draw attention to certain limitations and risks that may arise during the active use of this service. Emphasis is placed on the factors that restrain and inhibit the active process of introducing the Google Meet service into educational practice.
Kyselova O. Advantages and risks of using the google meet service for the conduct of online lessons / O. Kyselova, N. Khmil, L. Chetaieva // Enrichment of the pedagogical cluster of educational services : international collective monograph / edited by G. F. Ponomarova, A. A. Kharkivska, L. O. Petrychenko and other; Municipal Establishment «Kharkiv Humanitarian Pedagogical Academy» of Kharkiv Regional Council : Publishing house OKTAN PRINT s.r.o., 2022. – С. 379 - 393.
Keywords: онлайн-заняття, сервіс Google Meet, освітній процес, Інтернет, учитель; online lessons, Google Meet service, educational process, Internet, teacher